Bahasa Inggris - Hendrik Nemers; Rianti Dewi Sulamet-Ariobimo; Johny Wahyuadi Soedarsono; Muh. Fajar Ramadhan.; Agus Paul Setiawan Kaban; Ahmad Maksum; Theo Thomas; Djoko Nirprawitno (MBI, 2025)
Carbon is an essential element in the iron reduction process. Cokes are used as a carbon source in the traditional reduction process in the beneficiary of iron. When the Ironmaking Technology Mark 3 (ITMk3) method is applied in the reduction process, many carbon sources are used, especially the sources with sustainable and eco-friendly such as coconut shells, palm kernel shells, rice husk, and sugar cane bagasse. Saccharum officinarum or sugarcane extraction produced bagasse as the by-product. Like coconut shells, this rich carbon by-product is not utilized. This work discussed the utilization of bagasse as a reducing agent in the iron reduction process. An analysis is made based on specific reduction temperature with the various ratio of iron to coal. The lump ore is originated from South Borneo. Unlike the coconut shell, in this work, the Baggasse was dried. The process temperature range between 700 and 1000OC. The ratios of ore to bagasse were 1 to 1, 1 to 2, 1 to 3, and 1 to 4. The reduction process was carried out in a muffle furnace. The result shows that the reduction process produced wustite (FeO). This work also compared sugarcane bagasse with other green reducing agents.